Comparison of colour thresholding method using RGB and HSI information for Ziehl-Neelsen sputum slide images - Rafikha Aliana, A. Raof; Mohd Yusoff, Mashor, Prof. Dr.; R. Badlishah, Ahmad, Prof. Madya Dr.; Noor, S. S. M.; Kosman, M. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org